Application of a Zero-Valent Iron/Cork as Permeable Reactive Barrier for In Situ Remediation of Phenanthrene in Soil - Galvão, Álvaro G. P. (2022)
This paper proposes an eco-efficient treatment technology for removing phenanthrene (PHE) from kaolinite soil, incorporating a permeable reactive barrier (PRB) in an electrokinetic (EK) remediation system, which was made by modifying the granulated cork (GC) with Fe@Fe2O3, identified as EK/Fe@Fe2O3/GC. The novel product Fe@Fe2O3/GC was characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis, and element mapping. EK tests were conducted to investigate the performance of the EK/Fe@Fe2O3/GC for removal of PHE from soil. The results showed that PHE was driven by the electro-osmotic flow toward the cathode and reacted with the EK/Fe@Fe2O3/GC. Further, the removal efficiency of PHE in the soil was higher in the presence of H2O2 due to the additional reactions achieved. The results were discussed in light of the existing literature.